2003
DOI: 10.1086/502112
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Spinal Surgical-Site Infections in a Community Hospital: A Case–Control Study

Abstract: Dural tear and the use of glue should be evaluated as potential risk factors for spinal surgical-site infection. Systematic observation for potential lapses in sterile technique and surgical processes that may increase the risk of infection may help prevent spinal surgical-site infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
54
2
6

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(66 citation statements)
references
References 27 publications
4
54
2
6
Order By: Relevance
“…Five additional potentially relevant studies were identified from reference lists. Of the 34 articles that underwent full-text review, 12 [22][23][24][25][26][27][28][29][30][31][32][33] met eligibility criteria for inclusion in the meta-analysis and 22 were excluded. The most common reasons for exclusion of the 22 studies were: criteria for the diagnosis of SSI not reported and/or CDC/NNIS criteria not applied [34][35][36][37][38][39][40][41][42][43][44][45][46][47], non-scalar definitions of obesity used [47][48][49], risk estimates of the association between obesity/BMI and SSI not reported or raw data not provided to calculate risks [44,47,[50][51][52][53], and analyses restricted to deep wound infections [54,55].…”
Section: Literature Search and Systematic Review Resultsmentioning
confidence: 99%
“…Five additional potentially relevant studies were identified from reference lists. Of the 34 articles that underwent full-text review, 12 [22][23][24][25][26][27][28][29][30][31][32][33] met eligibility criteria for inclusion in the meta-analysis and 22 were excluded. The most common reasons for exclusion of the 22 studies were: criteria for the diagnosis of SSI not reported and/or CDC/NNIS criteria not applied [34][35][36][37][38][39][40][41][42][43][44][45][46][47], non-scalar definitions of obesity used [47][48][49], risk estimates of the association between obesity/BMI and SSI not reported or raw data not provided to calculate risks [44,47,[50][51][52][53], and analyses restricted to deep wound infections [54,55].…”
Section: Literature Search and Systematic Review Resultsmentioning
confidence: 99%
“…As one of the moderate-evidence factors, larger blood loss may be directly associated with blood transfusion, which results in immune suppression in the recipient [46] and an increased risk of infection for all types of surgery [4]. Previous surgery may result in bowel and bladder dysfunction or complex tissue reconstruction, which to some extent may increase the risk of SSI after The use of glue to cement the dural patch 13 [3] Postoperative incontinence 41 [39] Surgery for tumor resection 41 [39] Complete neurologic deficit 12 [48] Steroid therapy 22 [61] Extended preoperative hospitalization 22 [61] Indication for surgery 9 [34] Conflicting evidence The number of resident surgeons participating in the operative procedure 212 [5,26,40] spinal surgery. We also identified 31 limited-evidence factors, and only the number of resident surgeons participating in the operative procedure was identified as a conflicting-evidence factor.…”
Section: Discussionmentioning
confidence: 99%
“…In the setting of a surgical site infection, patients are likely to require intravenous (IV) antibiotics, a prolonged hospital stay 8 , and operative debridement. The deleterious clinical effects of surgical site infection are associated with an increase in total costs 1 .…”
mentioning
confidence: 99%
“…Estimates of the rate of surgical site infection following spine surgery have ranged from 1.9% to 13.8% [2][3][4][5][6][7][8]14 , depending on study design. Most studies on surgical site infection have included a retrospective analysis with matched control groups and have not adjusted for confounding factors [3][4][5][6][7] .…”
mentioning
confidence: 99%